The Construction of Legal Protection For Aesthetic Patients - Endang Sri Sarastri (Indian Journal of Forensic Medicine & Toxicology, 2021)
Plastic surgery, primarily aesthetic plastic surgery, is increasingly becoming one of the beauty proceduresthat is increasingly considered commonplace to be carried out by people in various countries in the world.When viewed from the sociological aspect of this aesthetic operation, it is solely aimed at improving thequality of life and utilizing science and technology, both of which, when linked from a legal perspective inIndonesia, is in line with the formulation contained in Article 28 C paragraph (1) of The 1945 Constitutionof the Republic of Indonesia as the state constitution of Indonesia. However, this aesthetic plastic surgeryencountered various obstacles; this can be proven from the problems that occurred with Mrs. P and Dr. W,where this case is related to the actions of Doctor W, who performed reconstructive and aesthetic surgeryon Mrs. P’s nose. For this case, Dr. W was threatened with unlawful acts for the medical actions he took.Therefore, this article will analyze the legal construction in Indonesia that regulates legal protection forplastic surgery patients. This article aims to find out and analyze how legal construction in Indonesia regulatesaesthetic plastic surgery. This is indicated to provide an understanding and test whether the medical actionof aesthetic plastic surgery can be said to be part of the scope of regulation regarding consumer protectionwhich is accommodated in Law No. 8 of 1999 or not. This research uses normative legal research methods.That is research conducted by examining library materials. The data used is secondary data, which includesprimary legal materials in statutory regulations, then also uses secondary legal materials that explain primarylegal custody. Construction of Legal Protection for Aesthetic Plastic Surgery consists of laws and regulationsrelating to the health/medical field that apply in Indonesia and the laws that apply in Indonesia, namely Lawno. 29 of 2004 concerning Medical Practice, Law No. 36 of 2009 concerning Health, Law Number 44 of2009 concerning Hospitals, Law Number 36 of 2014 concerning Health Workers, and the Civil Code: Article1313; 1319; 1320; 1330; 1333; 1337; 1338 and 1454, so that the provisions governing consumer protectionare not included in the scope for medical treatment.